Estresse e hardiness entre equipe multiprofissional do centro cirúrgico de um hospital universitário - Silva, Rosana de Oliveira Carvalho (2014)
Introduction: The occupational stress has received special attention from researcher, due to its influence on satisfaction, productivity, health and worker’s performance. In order to provide better stress confrontation at work, the hardiness personality comes out, improving coping faced to stress situations at work. It is associated to three personality’s dimensions: commitment, control and challenge. Objectives: identify the relationship between the stress intensity and hardiness among the surgery center’s multiprofessional team of a university hospital, in the city of Vitória, ES. Method: Cross-sectional and analytical study, which used quantitative approach and was carried out with 58 participants, all member of the surgery center’s multi professiona consisted on a questionnaire, containing socio-demographic characterization items, Workplace Stress Scale (WSS) and Hardiness Scale (HS). To analyze the data normality, the Shapiro-Wilk Test was used. To verify the association between the variables, parametric and non-parametric tests and the Spearman’s correlation coefficient was used. The significance level was 5% (0,050). The instruments internal consistency was analyzed using Conbrach’s alpha coefficient. Results: The results indicated moderate stress intensity in 55% of population and hardiness personality in 12% of participants. It was no statistically significant correlation found between the WSS and the HS, as well as in the tested variables. With regard of hardiness, 60,3% of professionals showed high level on HC, 62,1% low level on HCT and 58,6% high level on HD. HC showed significant correlation with the variables religion and work. HD showed statistically significant correlation with job, kids, age and length of service at the surgery center. HCT had statistically significant relationship with work shift. Conclusion: The team has a moderate intensity of stress. Socio- demographic characteristics and hardiness personality didn’t influence the stress’ perception in the surgery center’s multi professional team.